Semiconducting Polymer Dots with Modulated Photoblinking for High‐Order Super‐Resolution Optical Fluctuation Imaging. Issue 9 (18th February 2019) - Sun, Zezhou; Liu, Zhihe; Chen, Haobin; Li, Rongqin; Sun, Yujie; Chen, Danni; Xu, Gaixia; Liu, Liwei; Wu, Changfeng
Abstract: Super‐resolution optical fluctuation imaging (SOFI) uses photoblinking to achieve fast, background free, 3D fluorescence nanoscopy. The on/off photoblinking characteristics are key factors for realizing high‐order SOFI. However, it remains a great challenge to tune the photoblinking of a fluorescent probe because most of the probes are typical single fluorophore systems with stochastic blinking nature. In this study, effective photoblinking modulation is demonstrated in a nanoscale multichromophoric system consisting of donor–acceptor semiconducting polymers. Numerical simulation is performed to quantitatively evaluate the impact of the number of acceptors on the photoblinking of the nanoparticle probe as well as the spatial resolution of the resulting SOFI nanoscopy. In tandem with simulation, a series of polymer dots (Pdots) are designed with varying donor–acceptor moieties that give rise to the modulated photoblinking behaviors, as evidenced by single‐particle fluorescence trajectories. The photoblinking behaviors are quantitatively compared in terms of autocorrelation function, dot retention fraction, and on/off time ratio. High‐performance photoblinking‐based nanoscopy is implemented by using the optimized Pdots, resolving subcellular structure at a spatial resolution of ≈95 nm. This study provides a useful approach to engineer the photoblinking properties of fluorescent nanoparticles for super‐resolution imaging applications. Abstract : The on/off photoblinking characteristics are effectively modulated for semiconducting polymer dots. High‐order super‐resolution optical fluctuation imaging nanoscopy is demonstrated by using the photoblinking polymer dots, where subcellular structure can be resolved at a spatial resolution of ≈95 nm, a nearly fourfold increase as compared to the wide‐field image. This study provides a useful approach to engineer the blinking properties of fluorescent nanoparticles for super‐resolution applications.